Coaxial Multi-Wavelength Generation in YVO4 Crystal with Stimulated Raman Scattering Excited by a Picosecond-Pulsed 1064 Laser *Supported by the Key Laboratory Foundation from Technical Institute of Physics and Chemistry, Chinese Academy of Sciences. (14th April 2020) - Hao, Jing-Jie; Tu, Wei; Zong, Nan; Shen, Yu; Zhang, Shen-Jin; Bo, Yong; Peng, Qin-Jun; Xu, Zu-Yan
Abstract : The multiwavelength characteristics of stimulated Raman scattering (SRS) in YVO4 crystal excited by a picosecond laser at 1064nm are investigated theoretically and experimentally. Laser output with seven wavelengths is achieved coaxially and synchronously at 894, 972, 1175, 1312, 1486, 1713 and 2022nm in a YVO4 crystal. The maximum total Raman output energy is as high as 2.77 mJ under the pump energy of 7.75 mJ. A maximum total Raman conversion efficiency of 47.8% is obtained when the pump energy is 6.54 mJ. This is the highest order of Stokes components and the highest output energy generated by YVO4 reported up to date. This work expands the Raman spectrum of YVO4 crystal to the near-IR regime, with seven wavelengths covered at the same time, paving the way for new wavelength generation in the near-IR regime and its multiwavelength application.